2010
DOI: 10.1007/s12576-010-0085-z
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated Ca2+ channel mRNAs and T-type Ca2+ currents in rat gonadotropin-releasing hormone neurons

Abstract: Gonadotropin-releasing hormone (GnRH) neurons play a pivotal role in the neuroendocrine regulation of reproduction. We have previously reported that rat GnRH neurons exhibit voltage-gated Ca(2+) currents. In this study, oligo-cell RT-PCR was carried out to identify subtypes of the alpha(1) subunit of voltage-gated Ca(2+) channels in adult rat GnRH neurons. GnRH neurons expressed mRNAs for all five types of voltage-gated Ca(2+) channels. For T-type Ca(2+) channels, alpha(1H) was dominantly expressed in GnRH neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Consistent with published data in rat, we found that most of the HVA channel subtypes are expressed in mouse GnRH neurons with the R-type channel expression being the most prominent (Kato et al, 2003; Tanaka et al, 2010). Moreover Ca V 1.3 (L), Ca V 2.2 (N) and Ca V 2.3 (R) mRNAs, were significantly increased in E2-treated animals.. Interestingly, the HVA L - and N-type peak currents in GnRH neurons exhibit diurnal variation in E2-treated, but not in oil-treated mice, with reduced current amplitude in the morning and increased current amplitude in the evening (Sun et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with published data in rat, we found that most of the HVA channel subtypes are expressed in mouse GnRH neurons with the R-type channel expression being the most prominent (Kato et al, 2003; Tanaka et al, 2010). Moreover Ca V 1.3 (L), Ca V 2.2 (N) and Ca V 2.3 (R) mRNAs, were significantly increased in E2-treated animals.. Interestingly, the HVA L - and N-type peak currents in GnRH neurons exhibit diurnal variation in E2-treated, but not in oil-treated mice, with reduced current amplitude in the morning and increased current amplitude in the evening (Sun et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…There are four L-type channel isoforms (Ca V 1.1, 1.2, 1.3, 1.4), but only Ca V 1.2 and Ca V 1.3 have been reported in rat GnRH neurons (Tanaka et al, 2010). We confirmed that Ca V 1.2 and Ca V 1.3, but not Ca V 1.4, were expressed in mouse GnRH neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Harvesting single-cell mRNAs using patch pipettes is a well-established way to collect mRNA for RT-PCR from neurons, including GnRH neurons in various laboratories (Pape et al, 2001; Xu et al, 2008; Zhang et al, 2009, 2015; Tanaka et al, 2010; Bhattarai et al, 2011). In our present study, the mRNA content of the individual GnRH neurons of male mice used in PCR experiments was also harvested using the patch clamp pipette, as described earlier (Farkas et al, 2013; Vastagh et al, 2015) with slight modification.…”
Section: Methodsmentioning
confidence: 99%
“…As found in other neuronal systems, the role of I T is to initiate transient membrane depolarizations, which recruit high voltage-activated (HVA) calcium channels to increase calcium influx [39,40]. This is of functional significance since HVA calcium currents are prevalent in GnRH neurons [41], but they can only be activated from a more depolarized state, whereas low voltage-activated T-type currents are recruited from a more hyperpolarized state (i.e., they provide the signal for setting off burst firing) [32,38,41-44]. Importantly, the T-type Ca V 3.3 channel subunit expression and current density are significantly enhanced with a high LH surge-inducing E2 treatment, facilitating the excitation of GnRH neurons [32].…”
Section: E2 Modulation Of Gnrh Neuronal Activity Through Channel Exprmentioning
confidence: 99%